1992
DOI: 10.1002/1097-0142(19920315)69:6<1382::aid-cncr2820690614>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

The fibroma-like variant of epithelioid sarcoma

Abstract: Five cases of a previously undescribed variant of epithelioid sarcoma are presented. This variant differs from the usual lesion in its absence of the typical necrobiotic nodular epithelioid pattern. It is instead composed of deceptively bland fibrohistiocytic and myoid cells arranged in a fibroma‐like or dermatofibroma‐like pattern with an affinity for osseous involvement. The clinical presentation, ultrastructural features, and presence of vimentin and low molecular weight keratin within the tumor cells justi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(33 citation statements)
references
References 57 publications
0
33
0
Order By: Relevance
“…(1) dedifferentiation, (2) abrupt change to a higher grade sarcoma and (3) acquisition of differentiation 7 has not been reported in epithelioid sarcomas. This statement is also true for the fibroma-like variant of ES reported by Mirra et al 15 et al in 1992 in which bland spindle cell proliferation predominates in storiform or desmoid-like pattern. In the recurrent fibroma-like variant of ES Mirra et al 15 observed increasing anaplasia but not change in the histological appearance.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…(1) dedifferentiation, (2) abrupt change to a higher grade sarcoma and (3) acquisition of differentiation 7 has not been reported in epithelioid sarcomas. This statement is also true for the fibroma-like variant of ES reported by Mirra et al 15 et al in 1992 in which bland spindle cell proliferation predominates in storiform or desmoid-like pattern. In the recurrent fibroma-like variant of ES Mirra et al 15 observed increasing anaplasia but not change in the histological appearance.…”
Section: Discussionmentioning
confidence: 72%
“…This statement is also true for the fibroma-like variant of ES reported by Mirra et al 15 et al in 1992 in which bland spindle cell proliferation predominates in storiform or desmoid-like pattern. In the recurrent fibroma-like variant of ES Mirra et al 15 observed increasing anaplasia but not change in the histological appearance. In the second tumor of our case the spindle cells were pleomorphic and negative for epithelial markers, consequently the diagnosis of recidive ES with fibroma-like features could be excluded.…”
Section: Discussionmentioning
confidence: 76%
“…More than 2 decades ago, Mirra et al described five cases of a distinctive cytokeratin-positive soft tissue tumour characterised by multifocal involvement in a single limb [1]. Because the tumour commonly presents in the extremities of young patients, they suspected a variant of epithelioid sarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive immunohistochemical (IHC) studies by these authors suggested that these tumours were endothelial in origin rather than epithelioid tumours. Despite their multicentric and ominous presentation, they have been shown to generally behave in an indolent clinical manner at follow-up [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation